A single-tube-braided stent for various airway structures - Tong, Xin; Jiang, Yongkang; Mo, Fei; Sun, Zhongqing; Wu, Xiaojun; Li, Yingtian (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Airway stent has been widely used in airway procedures. However, the metallic and silicone tubular stents are not customized designed for individual patients and cannot adapt to complicated obstruction structures. Other customized stents could not adapt to complex airway structures with easy and standardized manufacturing methods. Object: This study aimed to design a series of novel stents with different shapes which can adapt to various airway structures, such as the “Y” shape structure at the tracheal carina, and to propose a standardized fabrication method to manufacture these customized stents in the same way. Methods: We proposed a design strategy for the stents with different shapes and introduced a braiding method to prototype six types of single-tube-braided stents. Theoretical model was established to investigate the radial stiffness of the stents and deformation upon compression. We also characterized their mechanical properties by conducting compression tests and water tank tests. Finally, a series of benchtop experiments and ex vivo experiments were conducted to evaluate the functions of the stents. Results: The theoretical model predicted similar results to the experimental results, and the proposed stents could bear a compression force of 5.79N. The results of water tank tests showed the stent was still functioning even if suffering from continuous water pressure at body temperature for a period of 30 days. The phantoms and ex-vivo experiments demonstrated that the proposed stents adapt well to different airway structures. Conclusion: Our study offers a new perspective on the design of customized, adaptive, and easy-to-fabricate stents for airway stents which could meet the requirements of various airway illnesses.